Assessment of CSR Practices in Nepalese Commercial Banks (A Comparative Study of RBBL, SCBL & NABIL) - Khanal, Kapil (Management Dynamics, 2019)
Objective: To assess the corporate social responsibility practices in Nepalese commercial banking sector. Methods and Materials: Primary and secondary sources of data were used in the study. The primary data were collected through direct questionnaire method from 60 employees of sampled commercial banks. The secondary source was through journals, textbooks and annual reports of Nepal Rastra Bank. SPSS and Microsoft excel were used to analyze the collected data. The value of Cronbach’s Alpha (α) of overall questionnaire is 0.92, which suggests the reliability of primary data. Descriptive and explorative research designs were used to analyze the primary and secondary data. Results and Conclusion: Responses from all the respondents of commercial banks regarding CSR and Non-Financial Performance clearly imply that CSR has an influence on the Non-Financial Performance. In terms of ‘R2’, CSR impacts both Brand Image and Brand Awareness (i.e. 0.987). This clearly indicates that more than 98.7% variance of both non-financial performances has been explained by CSR. In terms of ‘R2’, CSR impacts less in financial performance (i.e. 0.149). This clearly indicates that only than 14.9% variance of financial performance has been explained by CSR.